مساهمة شركات التأمين في دعم الاقتصاد الوطني في ظل أزمة وباء فيروس كورونا دراسة حالة الشركة الجزائرية للتأمين وإعادة التأمين Caar - ضيف, فارس (جامعة الوادي - University of Eloued, 2023)
لتأمين دور مهم في المجتمعات الحديثة، فهو يوفر الحماية للأفراد والممتلكات، وينشئ الأمن والأمان من الخسائر التي قد تلحق بالفرد في ماله وشخصه، كما يحتل مكانة هامة في اقتصاديات الدول، من خلال المساهمة في تحفيز النشاط الاقتصادي ودفع عجلة النمو. وفي ظل انتشار وباء فيروس كورونا وتخبط العالم وسط هذه الأزمة غير المسبوقة، تبذل جل الشركات التأمينية قصارى جهدها للوفاء بوعد الحماية. بما يتوافق مع تحقيق أهداف التنمية المستدامة. توصلنا من خلال هذه الدراسة الى أن قطاع التأمين في الجزائر يعاني تخلفا كبيرا وفقا لمؤشر معدل الاختراق والذي يترجم مساهمة نشاط التأمين في الناتج الداخلي الخام وكذا معامل كثافة التأمين والذي يعبر عن المعدل السنوي لما ينفقه الفرد على منتجات التأمين. Insurance has an important role in modern societies, as it provides protection for individuals and property, and creates security and safety from losses that may befall the individual in his money and person. It also occupies an important place in the economies of countries, by contributing to stimulating economic activity and advancing growth. In light of the spread of the Corona virus epidemic and the confusion of the world in the midst of this unprecedented crisis, most insurance companies are doing their best to fulfill the promise of protection. In line with achieving the goals of sustainable development. Through this study, we concluded that the insurance sector in Algeria suffers from a great backwardness according to the penetration rate index, which translates the contribution of insurance activity to the gross domestic product, as well as the insurance intensity coefficient, which expresses the annual rate of what the individual spends on insurance products
The contribution of insurance companies to support the national economy in light of the Corona virus epidemic crisis, a case study of the Algerian Insurance and Reinsurance Company CAAR
مقال
Keywords: التأمين ; النمو الاقتصادي ; معدل الاختراق ; فيروس كورنا; insurance, economic growth, penetration rate, insurance intensity, corona virus